2018
DOI: 10.3746/pnf.2018.23.4.356
|View full text |Cite
|
Sign up to set email alerts
|

Volatile Compounds in Seasoning Sauce Produced from Soy Sauce Residue by Reaction Flavor Technology

Abstract: Volatile flavor compounds created in the mixture of enzymatic hydrolysates of soy sauce residue and defatted soybean by reaction flavor technology (RFT) were analyzed and compared using solid phase micro-extraction/gas chromatography/mass selective detector to develop a seasoning sauce. Using response surface methodology analysis, RFT was performed by adding 0.50% fructose, 0.33% glutamic acid, 0.68% arginine, 0.37% methionine, and 0.86% glycine in the base and reaction conditions at 93°C for 120 min. A total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…It is worth mentioning that, due to its large surface area, high strength, high stability, excellent rheology, and emulsifying capacity, nanocellulose has been proven to be an effective alternative for restructuring meat and meat analogues. Researchers compared different samples with cellulose nanofibers (CNFs) either added or not, and found that, at the same fat level, samples added with CNF had a denser network, smaller cavities, and the structure became more continuous and compact, resulting in a better texture and reduced cooking loss [ 79 ]. It can be concluded that the rigid network formed by adding CNF is cross-linked with the protein matrix, which helps to obtain more fat droplets to form a more homogeneous structure.…”
Section: Chemical Restructuring Techniquesmentioning
confidence: 99%
“…It is worth mentioning that, due to its large surface area, high strength, high stability, excellent rheology, and emulsifying capacity, nanocellulose has been proven to be an effective alternative for restructuring meat and meat analogues. Researchers compared different samples with cellulose nanofibers (CNFs) either added or not, and found that, at the same fat level, samples added with CNF had a denser network, smaller cavities, and the structure became more continuous and compact, resulting in a better texture and reduced cooking loss [ 79 ]. It can be concluded that the rigid network formed by adding CNF is cross-linked with the protein matrix, which helps to obtain more fat droplets to form a more homogeneous structure.…”
Section: Chemical Restructuring Techniquesmentioning
confidence: 99%
“…There are various concepts for obtaining hemoglobin, which can be used as a substrate in the cultivation of muscle cells ( 20–22 ). The correct and acceptable perception of meat is linked to its olfactory qualities ( 23 ). Another important aspect is the fatty acid content ( 24 ).…”
Section: The History Of Cultured Meatmentioning
confidence: 99%
“…Another by-product is soy sauce residue (SSR), with about 4,500,000 tonnes of SSR is generated annually, and it is usually discarded without suitable application although it contains many nutrients such as proteins and oil. Limited studies have investigated the use of SSR protein as an efficient resource, for example, it can partly substitute defatted soybean to produce a seasoning sauce and can also be applied as a potential feedstock for biodiesel production (Wang & Cha, 2018;Xiang et al, 2019).…”
mentioning
confidence: 99%